Influence of the menstrual cycle phase on marathon performance in recreational runners - Greenhall, M.; Taipale, R. S.; Ihalainen, J. K.; Hackney, A. C. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To examine the potential impact of fluctuations in sex steroid hormones across the menstrual cycle (MC) on marathon running performance of recreational female athletes. Methods: A survey questionnaire was administered to recreational, nonelite runners who had completed multiple marathons within the last 18 months. Results: A total of 599 questionnaires were returned and deemed viable for review. From these, 185 survey participants were found to have complete information and eligibility to have their surveys used in the statistical analysis. A total of 106 women had their best marathon performance in the luteal phase (high sex steroid hormones) of the MC, and 79 had their best performance in the follicular phase (low sex steroid hormones) of the MC (responses were significantly different; z-score value = 1.11; P < .05). Conclusion: Recreational female runners have varying performances in the marathon across their MC phases, specifically performing better in the luteal phase of the cycle.